The new nobility: the restoration of Russia's security state and the enduring legacy of the KGB - Soldatov, Andrej Alekseevič (PublicAffairs, 2010)
In The New Nobility, two courageous Russian investigative journalists open up the closed and murky world of the Russian Federal Security Service. While Vladimir Putin has been president and prime minister of Russia, the Kremlin has deployed the security services to intimidate the political opposition, reassert the power of the state, and carry out assassinations overseas. At the same time, its agents and spies were put beyond public accountability and blessed with the prestige, benefits, and legitimacy lost since the Soviet collapse. The security services have played a central and often mysterious role at key turning points in Russia during these tumultuous years: from the Moscow apartment house bombings and theater siege, to the war in Chechnya and the Beslan massacre. The security services are not all-powerful; they have made clumsy and sometimes catastrophic blunders. But what is clear is that after the chaotic 1990s, when they were sidelined, they have made a remarkable return to power, abetted by their most famous alumnus, Putin